PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA OLLANDA BROWNIES RUMBAI PEKANBARU RIAU - Aysara, Fadhila; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research to find out how the influence of the marketing mix on purchasing decisions in order to achieve sales targets planned by Ollanda Brownies Rumbai Pekanbaru Riau and also to find out purchasing decisions in making purchases. The population in this study were consumers of Ollanda Brownies Rumbai Pekanbaru Riau by taking as many as 100 respondents using the census method. Research data in the form of primary data with a questionnaire as a research instrument and secondary in the form of company archives. Analysis of the data used is by using statistical analysis with the help of the SPSS program. Based on the results of research conducted the authors draw conclusions on the marketing mix influence on purchasing decisions on Ollanda Brownies Rumbai Pekanbaru Riau from the responses of the respondents studied that each has indicators that are interrelated and influence the purchasing decisions on Ollanda Brownies Rumbai Pekanbaru Riau.